Ispol'zovanie vysokogor'ja i adaptogenov v podgotovke sbornoj SSSR po vol'noj i greko-rimskoj bor'be k Olimpijskim igram v Mechiko - Zakharov, A. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
This article discusses the use of adaptogens and highland conditions during the preparation of the USSR team in Greco-Roman and freestyle wrestling for the Olympic Games in Mexico City. The analysis of the means applied and a used method is given. The differences between the control and experimental groups are described in the article. The article describes the method of shutting down analyzers, and also draws conclusions about the beneficial effects of the techniques used in the preparation.